(3OjhGf TYQs ((3EOQjSj Hf Ydj Hf EHQGgje Hf QGTO GdYdhj s)
(3ChdgG (B:s
(3eHJhQ Chdg hjHOC CKfGA bGajI GdHGA Hbhdg(B: (3jSYhf fMh gVGH jGWGH ehQOgG cCfeG GdYPH eTJb ef GdYPH s
(3BNQgG (B:s
(3bhdg(B: (3Ef bSJg HGdTeS aj MSfg aGdTeS aj bHVg cajg GfJgi TYQg QMeg Gddg s
(3Vef eLehY , JQJjHgG (B: (3ef U (B1 - (3U(B26s
(3jdjg ehTMGJ aj UaMJjf ef fXe UGMH GdOjhGfs
(3heQJH Ydi MQha GdgLGAs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GdCOHs